Gorlov Water Turbine Application in Ambon, Kepulauan Maluku; A Hypothetical Project - Wisnu Wardhana; Zahra Aisyiyah Rahayu; Shade Rahmawati (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2022)
As energy demand increases, it must be balanced with sufficient energy sources to support the growth of Indonesia's electrification ratio. No exception with the development of energy demand and supply on Ambon, Maluku Islands. This study uses a Renewable Energy Power Plant, a water turbine that uses ocean currents from the flow path of an artificial canal plan in Ambon, Maluku Islands. The shape of the area is interesting things to make an artificial canal as a flow path for ocean currents from the different height at that location. Due to the height difference cannot be determined with certainty, in this study, the authors vary the height difference between the sea in the east and west, it's 1m to 5m. Current modelling uses a numerical approach using the Surface-Water Modeling System (SMS) 8.1 software simulation. Then the average current velocity in the canal in each height variation obtained. The experimental data from journal references are used in calculating the turbine torque for a full-scale afterwards adjusted to the current speed generated in each variation. The turbine with the greatest torque is selected, owned by the 4-blades Gorlov NACA0012 with 25% efficiency and 9.5m turbine diameter totalling 1 unit.